2020
DOI: 10.1186/s12889-020-09069-7
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure, reporting and help seeking among child survivors of violence: a cross-country analysis

Abstract: Background: Violence against children is a pervasive public health issue, with limited data available across multiple contexts. This study explores the rarely studied prevalence and dynamics around disclosure, reporting and helpseeking behaviours of children who ever experienced physical and/or sexual violence. Methods: Using nationally-representative Violence Against Children Surveys in six countries: Cambodia, Haiti, Kenya, Malawi, Nigeria and Tanzania, we present descriptive statistics for prevalence of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 31 publications
2
38
0
2
Order By: Relevance
“…Based on data from 30 countries, only 1 per cent of adolescent girls who have experienced forced sex reached out for professional help ( United Nations Children’s Fund, 2017 ). A secondary analysis of nationally-representative Violence Against Children Surveys data in six countries concluded that the prevalence of help-seeking behaviours ranged from 23 per cent to 54 per cent for informal disclosure, from 16 per cent to 28 per cent for knowledge of where to seek formal help, from under 1 per cent to 25 per cent for formal disclosure or help-seeking, and was only between 1 per cent and 11 per cent for receipt of formal help ( Pereira et al, 2020 ). While primary reasons for not seeking help varied by country, the most common ones included self-blame, apathy and not needing or wanting services.…”
Section: Introductionmentioning
confidence: 99%
“…Based on data from 30 countries, only 1 per cent of adolescent girls who have experienced forced sex reached out for professional help ( United Nations Children’s Fund, 2017 ). A secondary analysis of nationally-representative Violence Against Children Surveys data in six countries concluded that the prevalence of help-seeking behaviours ranged from 23 per cent to 54 per cent for informal disclosure, from 16 per cent to 28 per cent for knowledge of where to seek formal help, from under 1 per cent to 25 per cent for formal disclosure or help-seeking, and was only between 1 per cent and 11 per cent for receipt of formal help ( Pereira et al, 2020 ). While primary reasons for not seeking help varied by country, the most common ones included self-blame, apathy and not needing or wanting services.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Analyses of the Violence Against Children Surveys in six countries showed that the self-reported prevalence of physical violence was at least 60% and of sexual violence at least 10%, while formal disclosure of physical and/or sexual violence ranged from 1% to 25%. 15 Interviewing children and young people about violence is also central to a commitment to child participation, which emphasises the pivotal role of children in research that concerns their lives. 16–18 …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there is also a clear need for interventions to address the tendency in this setting to hold children accountable for abuse, alongside approaches that address unequal gender norms that underpin blame for girls experiencing sexual exploitation and abuse. Blame and stigmatisation leaves children unsupported, strengthens inequalities and, further, underpins children’s reluctance to come forward [ 15 , 63 , 64 ]. Violence in schools, and responses to it, are closely related to gender norms and inequalities, and require gender-sensitive policy and intervention approaches [ 27 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also in Zimbabwe, amid contexts of adversity where teachers themselves face unresolved challenges, teachers can feel overburdened, demoralised and even resentful of children [7,9], and that their own painful experiences are overlooked [6]. Some studies in sub-Saharan African settings show the potential of schools as sites for disclosure and referral to social and health services [10,15,16], or as sites for violence prevention interventions [15,17], however, also highlighting the support, resources and improvements to many schools' everyday functioning needed to operationalise this [10,13,14]. Sociological studies of education also emphasise how schools are sites wherein gendered norms, inequalities and identities can be both formed and reinforced, and that this shapes teachers' interactions with children around violence, as examined in sub-Saharan Africa [18][19][20][21][22], and in Zimbabwe [23,24].…”
Section: Introductionmentioning
confidence: 99%